A Study Of Structure Breaks In Amman Stocks Market By Using Wavelet Transform. - Al Wadi, S.; Ismail, Mohd Tahir; Ariffin Addul, Samsul (2009)
Regime shifts or structure breaks acquire very high attention in analyzing financial time series data.